1987
DOI: 10.1001/jama.1987.03400060061029
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Immunodeficiency Syndrome in Low-Incidence Areas

Abstract: Serum specimens from the cohort of persons who attended sexually transmitted disease clinics in New Mexico during a two-month period were tested for human immunodeficiency virus (HIV) antibody. Twenty-seven (2.0%) of 1374 serum specimens had repeatedly low-positive reactions by enzyme-linked immunosorbent assay testing, and 22 (1.6%) had repeatedly high-positive reactions. All sera (sufficient for testing by Western blot) with low-positive reactions gave negative results, and all sera (sufficient for testing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Specimens that are repeatedly reactive on the EIA should be confirmed by the HIV-1 Western blot (immunoblot) assay. False-positive results on the EIA have been shown to occur in patients with a positive rapid plasma reagin test (37), hemophiliac patients (92), and patients on hemodialysis (77). Kuhnl et al have also detected cross-reacting antibodies to HLA DR4 antigen (found in H9 cell lines) which seroreact when tested by EIA (56).…”
Section: Serological Methods For Detection Of Hiv-1mentioning
confidence: 99%
“…Specimens that are repeatedly reactive on the EIA should be confirmed by the HIV-1 Western blot (immunoblot) assay. False-positive results on the EIA have been shown to occur in patients with a positive rapid plasma reagin test (37), hemophiliac patients (92), and patients on hemodialysis (77). Kuhnl et al have also detected cross-reacting antibodies to HLA DR4 antigen (found in H9 cell lines) which seroreact when tested by EIA (56).…”
Section: Serological Methods For Detection Of Hiv-1mentioning
confidence: 99%
“…These false-positive results can be due to intrinsic variability in test performance, heat inactivation of serum, HLA antibodies with specificity for HLA DQ3 and DR4 antigens (found in the H-9 cell line used to grow stock virus), and probably other contaminating antigens from cell lines (12,71). False-positive EIA results have been reported to be as high as 19% in hemophilia patients (113), 13% in alcoholic patients with hepatitis (83), 4% in hemodialysis patients (96), and 24% in patients who have a positive rapid plasma reagin test (41). Therefore, confirmatory testing of all EIA repeatedly reactive specimens is essential.…”
Section: Eiamentioning
confidence: 99%